1991
DOI: 10.1007/bf01344341
|View full text |Cite
|
Sign up to set email alerts
|

Shell growth response of mussels (Mytilus edulis) exposed to toxic microalgae

Abstract: Abstract. Mussels (Mytilus edulis) were exposed to the algae Alexandrium ostenfeldii, Chrysochromulina polylepis, Gyrodinium aureolum, Gymnodinium galatheanum and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 12 publications
2
24
0
Order By: Relevance
“…For example a 1950 fish kill in Walvis Bay, South Africa was attributed to Gyrodinium galatheanum (Copenhagen, 1953;Braarud, 1957;Pieterse and Van Der Post, 1967). Laboratory experiments showed this organism causes mortality in juvenile cod and reduced growth in mussels (Nielsen and Strømgen, 1991;Nielsen, 1993). In Alfacs Bay, Spain, Gyrodinium corsicum (Paulmier et al, 1995) was implicated in killing of Sparus aurata Linnaeus (gilthead seabream) in aquaculture ponds (Delgado, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…For example a 1950 fish kill in Walvis Bay, South Africa was attributed to Gyrodinium galatheanum (Copenhagen, 1953;Braarud, 1957;Pieterse and Van Der Post, 1967). Laboratory experiments showed this organism causes mortality in juvenile cod and reduced growth in mussels (Nielsen and Strømgen, 1991;Nielsen, 1993). In Alfacs Bay, Spain, Gyrodinium corsicum (Paulmier et al, 1995) was implicated in killing of Sparus aurata Linnaeus (gilthead seabream) in aquaculture ponds (Delgado, 1998).…”
Section: Introductionmentioning
confidence: 97%
“…Indicates grab-sampl~ng area ratory experiments have shown toxic effects of Chrysochromulina polylepis on eggs and larvae of the ascidian Ciona intestinalis (Granmo et al 1988), blue mussel Mytilus edulis (Granmo et al 1988, Nielsen & Stramgren 1991 and on the nauplii of the crustacean Artemia salina (Edvardsen & Paasche 1992). The toxin seems to be similar to prymnesin, the toxin produced by Prymnesium, In its haemolytic and cytotoxic characteristics resulting from interaction with cell membranes (Shilo 1981, Underdal et al 1989, Yasomoto et al 1990).…”
Section: "mentioning
confidence: 99%
“…Different studies have demonstrated that toxic dinoflagellates produce sub-lethal effects in some filter-feeding organisms, affecting byssus production and oxygen consumption, and also reducing feeding activity, which may even be stopped completely due to the closure of the valves Marsden and Shumway 1993). The dinoflagellate Gyrodinium aureolum produces a reduction in the clearance and growth rates, as well as intestinal damage, when it is ingested by the bivalve Mytilus edulis (Nielsen and Strömgren 1991).…”
Section: Introductionmentioning
confidence: 99%